AD, Volume 37, n° 3, 2012 - Full Issue (Africa Development, 2021)
Contents Introduction: Parents’ Involvement in Children’s Lives in Africa Mwenda Ntarangwi ................................ 1 Dating Practices and Patterns of Disclosure among in-School Adolescents in Oyo State, Nigeria Agunbiade Ojo Melvin ............................ 19 Parent-Child Communication on Sexuality-Related Matters in the City of Lagos, Nigeria Michael O. N. Kunnuji ............................. 41 Mothers’ Constructions of their Roles in the Literacy Education of their Children Ngozi Anyikwa & Ngozi Obidike ............ 57 Parents’ Engagement in Adult Literacy and its Impact on their Children’s Schooling Efua Irene Amenyah .................... 69 From the Will to the Field: Parent Participation in Early Childhood Education in Madagascar Colleen Loomis & Abdeljalil Akkari .............. 87 Husbands in Wives’ Shoes: Changing Social Roles in Child Care among Cameroon’s Urban Residents Henry Kam Kah ................. 101 Where is my Daddy? An Exploration of the Impact of Absentee Fathers on the Lives of Young People in Botswana Gloria Thupayagale-Tshweneagae, Tennyson Mgutshini & Zethu Zerish Nkosi............ 115 Children’s Experiences of Support received from Men in Rural KwaZulu-Natal Tawanda Makusha, Linda Richter & Deevia Bhana ........... 127 Latchkey Experiences of School-Age Children in Low-income Families in Akwa Ibom State, Nigeria Mildred Ekot..........................153 ‘Arming the Rebels for Development’: Parental Involvement among Fishing Communities in Tanzania Paul Wabike ......................... 171 Forced into Adulthood: An Exploration of Psycho-Social Dynamics in Child Headed Households Bernadette Muyomi ....................... 193